Degree of style coiling is associated with corolla-tube length in the nectarless flowers of Roscoea schneideriana - Bo Wang; Ze-Yu Tong; Ying-Ze Xiong; Xiao-Fan Wang; W. Scott Armbruster; Shuang-Quan Huang (Plant Diversity, 2023)
The plant-pollinator ‘arms race’ model posits that a major driver of the evolution of elongated corollas in flowers is reciprocal selection for ‘morphological fit’ between pollinator-tongue length and access distance to nectar (usually corolla-tube length). Evidence for the pollinator-mediated selection on tube length and evolution of multiple, correlated floral traits remains inconclusive. To gain possible insights into the strength of stabilizing selection by assessing standing phenotypic variation, we measured a series of functionally important floral traits, including corolla tube length and ‘effective’ tube depth and degree of style coiling. We then calculated coefficients of variation (CV) for these traits in three field populations of R. schneideriana. Unlike in most long-tubed flowers, the bottom part of the corolla tube is completely occupied by the style, with no room for nectar. The length of this portion of the corolla tube was more variable (higher CV) than the upper part of the corolla tube, suggesting that functional tube depth was under stronger stabilizing selection. The degree of style coiling was negatively related to the corolla-tube length in all three populations of R. schneideriana, suggesting that there may be conflicting selection acting on style length and corolla-tube length, which are otherwise usually tightly correlated. Given the lack of nectar in the flowers of this species, the long corolla tubes and long styles may represent morphological holdovers from ancestors that were pollinated by long-tongued pollinators, as is still seen in related species in the western Himalayas.